Approaching glioblastoma during COVID-19 pandemic: current recommendations and considerations in Brazil - Gabriel Novaes de Rezende Batistella; Adrialdo José Santos; Manoel Antonio de Paiva Neto; Robson Ferrigno; Veridiana Pires de Camargo; João Norberto Stavale; Marcos Vinicius Calfat Maldaun (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Cancer patients in general and glioblastoma patients, in particular, have an increased risk of developing complications from the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and reaching a balance between the risk of exposure to infection and the clinical benefit of their treatment is ideal. The aggressive behavior of this group of tumors justifies the need for a multidisciplinary team to assist in clinical decisions during the current pandemic. Brazil is now ranked #2 in the number of cases and deaths from COVID-19 pandemic, and existing disparities in the treatment of neuro-oncology patients in Brazil will challenge the clinical and surgical decisions of this population, possibly affecting global survival. Objective: To search the literature about the management of glioblastomas during COVID-19 pandemic to guide surgical and clinical decisions in this population of patients in Brazil. Methods: We performed a systematic search on the PubMed electronic database targeting consensus statements concerning glioblastoma approaches during COVID-19 pandemic up to July 18, 2020. Results: When approaching glioblastoma during the COVID-19 pandemic, important parameters that help in the decision-making process are age, performance status, tumor molecular profile, and patient consent. Younger patients should follow the standard protocol after maximal safe resection, mainly those with MGMT methylated tumors. Aged and underperforming patients should be carefully evaluated, and probably a monotherapy scheme is to be considered. Centers are advised to engage in telemedicine and to elaborate means to reduce local infection. Conclusion: Approaching glioblastoma during the COVID-19 pandemic will be challenging worldwide, but particularly in Brazil, where a significant inequality of healthcare exists.